Urban Growth Dynamics in the New Capital of North Maluku: A Spatiotemporal Perspective on Land Cover Transformation in Sofifi - Aginda, M. Fadel; Hasibuan, Hayati Sari; Tambunan, Rudy Parluhutan; Falensky, Muhammad Attorik; Wicaksono, Satrio Rifqi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
The transition of North Maluku Province's capital city from Ternate to Sofifi in Halmahera Island is expected to spawn a new growth center. However, the development and expansion of urban areas in Sofifi reflect significant land cover transformation. This process is shaped by complex interactions influenced by the island’s geographical context and limited environmental carrying capacity. To ensure the sustainability of urban growth dynamics in Sofifi, this study aims (1) identify and analyze the spatiotemporal dynamics of land cover transformation from 1995 to 2020 in Sofifi and (2) analyze the growth pattern of urban expansion in Sofifi. This study employed multitemporal Landsat imageries within the 1995 to 2020 period with supervised classification using the CaRT classifier in Google Earth Engine and the NDBI maps to calculate the urban expansion rate and intensity index. The multitemporal analysis shows the rapid transformation of vegetation cover into built-up areas, especially in the 2010–2015 periods, which gradually developed from coastal areas towards inland following the development of road networks and government offices. The spatial expansion index shows the average urban growth in Sofifi from 1995 to 2020 is about 28.61%. This study reveals that the transformation of Sofifi land cover is shifting the vegetation cover to the built-up area by 967 hectares (27.61% of the Sofifi Area) from 1990 to 2020. Parallelly, urban expansion happens in stages. Moreover, this research advances the understanding of how land cover transformation and urban expansion happened in the island cities, particularly in the Indonesian context.